Financing apprenticeship training: Evidence from Germany - Harhoff, Dietmar [Verfasser]; Kane, Thomas J. [Verfasser] (My University, 1993)
"Much of the current discussion promoting apprenticeship programs in the U.S. proceeds as if it is simply a matter of historical accident or lack of imagination which has hindered human capital investment by U.S. firms. However, the cause may be rooted more deeply in our labor market institutions. This paper discusses the structure of incentives undergirding the German system of apprenticeship training. Many German firms face large net costs of apprenticeship training. Yet they continue to provide such training in spite of considerable worker turnover upon completion of the training. The simplest human capital model suggests that employers would be willing to finance only firm-specific training. Rather than engage in a futile debate over the general or specific nature of the skills being provided, we first describe and evaluate 3 characteristics of the German labor market which may lead firms to accept part of the cost of general training even in the face of worker turnover. We then attempt to understand why German workers and firms may be more willing to invest even in firm-specific skills than in the U.S. Finally, we discuss some implications of these results for the current vocational training debate in the U.S." (Autorenreferat, BIBB-Doku)
Keywords: S 4.1 Finanzierungsquellen; S 4.3.6 Human Capital; Betriebliche Berufsausbildung; Bildungsfinanzierung; Bildungsinvestition; Bildungsertrag; Bildungsökonomie; Bundesrepublik Deutschland; USA